2018
DOI: 10.1016/j.cardfail.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endurance Training on Detrimental Structural, Cellular, and Functional Alterations in Skeletal Muscles of Heart Failure With Preserved Ejection Fraction

Abstract: Obesity-related HFpEF was associated with detrimental structural, cellular, and functional alterations to both slow-oxidative and fast-glycolytic skeletal muscles that could not be reversed by endurance training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 34 publications
5
27
0
Order By: Relevance
“…This allowed various sites in the muscle contractile process to be evaluated for dysfunction in HFpEF, including neuromuscular transmission and excitation-contraction coupling. Consistent with previous data where absolute maximal soleus force was reduced by ∼20% in HFpEF rats vs. controls (Bowen et al 2018;Schauer et al 2020), we observed that absolute twitch and maximal forces in both the soleus and EDL were lower in HFpEF rats. However, limb muscle weakness was closely associated with fibre atrophy as, after normalising for muscle mass, specific forces were not different between groups independent of whether the neural and blood supply remained intact.…”
Section: Impact Of Hfpef On Limb Muscle Functionsupporting
confidence: 92%
See 2 more Smart Citations
“…This allowed various sites in the muscle contractile process to be evaluated for dysfunction in HFpEF, including neuromuscular transmission and excitation-contraction coupling. Consistent with previous data where absolute maximal soleus force was reduced by ∼20% in HFpEF rats vs. controls (Bowen et al 2018;Schauer et al 2020), we observed that absolute twitch and maximal forces in both the soleus and EDL were lower in HFpEF rats. However, limb muscle weakness was closely associated with fibre atrophy as, after normalising for muscle mass, specific forces were not different between groups independent of whether the neural and blood supply remained intact.…”
Section: Impact Of Hfpef On Limb Muscle Functionsupporting
confidence: 92%
“…Recent investigations, therefore, have suggested non-cardiac 'peripheral' factors as major mechanisms limiting functional capacity and quality of life in patients with HFpEF, with skeletal muscle abnormalities receiving much attention (Adams et al 2017;Poole et al 2018;Zamani et al 2020). For example, animal and human studies have shown that HFpEF is associated with various skeletal muscle impairments that are closely associated with exercise intolerance and lower quality of life, including lower skeletal muscle mass and strength (Bekfani et al 2016), generalised fibre atrophy (Bowen et al 2018), fat infiltration Zamani et al 2020), reduced global capillary-to-fibre ratio (Kitzman et al 2014;Bowen et al 2018), reduced mitochondrial function and content (Bowen et al 2015;Molina et al 2016;Bowen et al 2017b), disrupted high-energy phosphate metabolism (Bhella et al 2011b;Weiss et al 2017), and impaired O 2 extraction (Dhakal et al 2015;Houstis et al 2018;Zamani et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…75,162,163 More recently this line of research included a more clinically relevant animal model, in the way that HFpEF develops due to the onset of multiple comorbidities that mirror a metabolic syndrome. 76,164166 Another problem with appropriate animal models may be that most models develop over a short time period, whereas in humans several years or decades sometimes pass before a clear phenotype is established.…”
Section: Challenges and Opportunities In Translational Cr Research Mementioning
confidence: 99%
“…Any imbalance between these multiple signaling pathways during aging results in loss of muscle mass and function. Recent findings have reported that impaired autophagy in skeletal muscle is seen in HF animal models, which may contribute to skeletal muscle damage and degeneration [ 45 , 46 , 47 , 48 ]. Thus, autophagy signaling must be properly regulated to maintain skeletal muscle quality and quantity in HF patients.…”
Section: Potential Mechanisms Of Sarcopenia In Heart Failurementioning
confidence: 99%